PERAN BATUAN DASAR TPA DALAM MEREDUKSI PENYEBARAN AIR LINDIAN SAMPAH (LEACHATE) SECARA ALAMIAH DI DAERAH BEKAS TPA PASIR IMPUN - -, T. Yan W. M. Iskandarsyah (Bulletin of Scientific Contribution, 2007)
This research was conducted at Pasir Impun Landfill Site which had an unperfect sanitary landfill system, so that the groundwater contamination occurred in the surroundings area. In order to minimize the spreading of leachate as natural, basement rock properties of landfill site could be an important factor. Generally, the basement rock of Pasir Impun Landfill Site had a good geological characteristic, eventhough there was a poor value of hydraulic conductivity between 10-4 - 10-5 cm/sec (>10-7 cm/sec; minimum value for a good landfill site). The good basement rock properties of Pasir Impun Landfill Site were (i) the basement rock had a deep groundwater table, (ii) a highly clay content in the basement rock which caused a rising retardation factor. Procentage of clay mineral (kaolinite) in the basement rock of this landfill site could be 87,22 %, with the value of retardation factor was 2,63. On the other side, the poor value of dispersion at the Pasir Impun Landfill Site showed that natural attenuation did not occure yet intensively. So, it could be predicted for 10 years later that the leachate plume will bigger than now, but still in 200 meter radius of leachate spreading.